Torsade de Pointes Induced by Hypokalemia from Imipenem and Piperacillin - Varun Kumar; Sandeep Khosla; Monica Stancu (Case Reports in Cardiology)
Imipenem-cilastatin and piperacillin-tazobactam are two antibiotics with broad antimicrobial coverage. Besides the many well established adverse effects of these drugs, there have been few case reports of hypokalemia. Here we present an interesting case of resistant hypokalemia caused by these drugs leading to Torsades de Pointes which has never been reported in the past. Hypokalemia resolved with discontinuation of piperacillin.